2009
DOI: 10.17221/23/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of IBV structural proteins and chicken interleukin-2 for DNA immunization

Abstract: ABSTRACT:The S1 gene of IBV and the chicken IL-2 gene were ligated together into a eukaryotic expression vector pCI-neo for co-expression evaluation in vitro. The recombinant plasmids were transfected into Vero cells, and the expression of targeted proteins was confirmed by an indirect immunofluorescent assay and immunocytochemistry assay. By repeating intramuscular injection several times, the co-expression plasmids provided chicks with some immune protection against viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Vaccination with DNA vaccines, also known as third-generation vaccines, is a promising approach for the effective control of many diseases in the fields of veterinary medicine and food animal production (7,8). Recently, several studies have shown that DNA vaccines can elicit protective immune responses against IBV (1,14,18,42), with the intramuscular route of injection being the most common route of DNA vaccination in avian species. However, the cost constraints involved with livestock production and the need for mass immunization have limited the application of DNA vaccines to the commercial poultry industry.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with DNA vaccines, also known as third-generation vaccines, is a promising approach for the effective control of many diseases in the fields of veterinary medicine and food animal production (7,8). Recently, several studies have shown that DNA vaccines can elicit protective immune responses against IBV (1,14,18,42), with the intramuscular route of injection being the most common route of DNA vaccination in avian species. However, the cost constraints involved with livestock production and the need for mass immunization have limited the application of DNA vaccines to the commercial poultry industry.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular immune response is improved after intramuscular administration of DNA vaccines expressing the nucleoprotein N with IL2 which increase the IgG titer, the percentage of LT and the level of protection compared to vaccines expressing only the N protein (Tang et al, 2008). The maximum clinical and necrotic protection of chickens (up to 70%) is obtained with repeated intramuscular injections of plasmids co-expressing IL2 and S1 (Zhang et al, 2009).…”
Section: Adjuvantsmentioning
confidence: 99%